Kesantunan Berbahasa Siswa Jurusan Perhotelan Kelas XI SMK Negeri Padang 9 dengan Guru Bahasa Indonesia melalui Media Sosial WhatsApp - Andriani, Dini Putri; Arief, Ermawati; R, Syahrul; Satria, Dadi (Universitas Muhammadiyah Magelang, 2026)
This study aims to describe the forms of compliance and violations of the principles of politeness of language among students in communicating with Indonesian language teachers through social media WhatsApp based on the communication context according to Hymes' theory. This study uses a qualitative approach with descriptive methods. The research data are in the form of written utterances of students to Indonesian language teachers obtained from WhatsApp messages in the 2024/2025 academic year. The data collection technique was carried out using the documentation method, while the data analysis technique was carried out by grouping the data based on compliance and violations of the principles of politeness of language according to Leech's politeness theory and examined based on Hymes' SPEAKING context components. The results showed that of the 30 student utterances analyzed, there were 21 utterances that complied with the principles of politeness of language and 9 utterances that violated the principles of politeness of language. The analysis of the communication context showed that in general, student utterances took place in a polite communication context and were in accordance with the norms of language interaction, although there were still some utterances that did not comply with the principles of politeness of language. Based on the results of this study, it can be concluded that students' politeness of language in communicating with teachers through social media still needs to be improved. Therefore, an understanding of the principles of politeness is important to instill in educational settings to create more polite, effective, and socially normative communication.